2015
DOI: 10.1080/02640414.2015.1061201
|View full text |Cite
|
Sign up to set email alerts
|

Assessing personal talent determinants in young racquet sport players: a systematic review

Abstract: Since junior performances have little predictive value for future success, other solutions are sought to assess a young player's potential. The objectives of this systematic review are (1) to provide an overview of instruments measuring personal talent determinants of young players in racquet sports, and (2) to evaluate these instruments regarding their validity for talent development. Electronic searches were conducted in PubMed, PsychINFO, Web of Knowledge, ScienceDirect and SPORTDiscus (1990 to 31 March 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 44 publications
3
64
0
6
Order By: Relevance
“…With the exception of the studies by Huijgen et al (2015) and Verburgh et al (2014), most studies on the relation between higher-level cognitive functions and sport performance focused on adolescent or adult players [ 9 , 10 ]. However, in terms of talent identification and talent development, it seems essential to acquire knowledge on youth players as well, preferably applying a multidimensional, longitudinal design [ 36 , 37 ]. Elementary forms of executive functions are present as early as the preschool period (3–5 years) and develop from early childhood through adolescence into young adulthood [ 28 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the studies by Huijgen et al (2015) and Verburgh et al (2014), most studies on the relation between higher-level cognitive functions and sport performance focused on adolescent or adult players [ 9 , 10 ]. However, in terms of talent identification and talent development, it seems essential to acquire knowledge on youth players as well, preferably applying a multidimensional, longitudinal design [ 36 , 37 ]. Elementary forms of executive functions are present as early as the preschool period (3–5 years) and develop from early childhood through adolescence into young adulthood [ 28 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the option "not applicable" allowed an appropriate score for the article, eliminating the negative effect of assuming the value "0" on a binary scale, when in fact that specific item was not applicable to that study. As in previous research [11,12], to make a fair comparison between studies of different designs, the decision was taken to calculate a percentage score as a final measure of methodological quality. For this, the sum of the score of all items was divided by the number of relevant scored items for that specific research design.…”
Section: Extraction Of Data and Quality Of The Studiesmentioning
confidence: 99%
“…Today, many national federations select young athletes via talent identification / development programs and follow up their progress [12][13][14]. Most of the skill tests used in these talent identification and development programs assess perceptive and motor skills [15][16][17]. However, due to the fact that mental and cognitive skills play a more significant part in athletic achievement, tests that assess cognitive skills in particular has attracted significant attention recently [18][19][20].…”
mentioning
confidence: 99%
“…Most cognitive tests are applied either desk-bound or as simulation tests and are far from the ecologic nature of sports [21,22]. In addition, it is suggested that all skills (perceptive, motor and cognitive) must be evaluated by tests that mimic all components of performance in sports [23,24]. However, to the best of our knowledge, no method that evaluates cognitive skills along with perception and motor skills in a single test has been published yet in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation